2006
DOI: 10.2527/jas.2006-038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vasoconstrictive potential of D-lysergic acid using an isolated bovine lateral saphenous vein bioassay1

Abstract: Vasoconstriction has been associated with several symptoms of fescue toxicosis thought to be alkaloid induced. Lysergic acid, an ergot alkaloid, has been proposed as a toxic component of endophyte-infected tall fescue. The objective of this study was to examine the vasoconstrictive potential of D-lysergic acid using a bovine lateral (cranial branch) saphenous vein bioassay. Before testing lysergic acid, validation of the bovine lateral saphenous vein bioassay for use with a multimyograph apparatus was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 12 publications
7
70
1
Order By: Relevance
“…However, a series of studies have been published recently that examined the potency and efficacy of selected ergot alkaloids to induce constriction of the bovine lateral saphenous vein in vitro (Klotz et al, 2006(Klotz et al, , 2007(Klotz et al, , 2008(Klotz et al, , 2010. Ergovaline was shown to be approximately 1,000-fold more potent and 5-fold more efficacious in causing vasoconstriction than lysergic acid (Klotz et al, 2006(Klotz et al, , 2007. Ergotamine and ergovaline reportedly have very similar contractile dose response curves (Klotz et al, 2007).…”
Section: Vasoconstrictive Potency and Efficacy Ofmentioning
confidence: 96%
See 1 more Smart Citation
“…However, a series of studies have been published recently that examined the potency and efficacy of selected ergot alkaloids to induce constriction of the bovine lateral saphenous vein in vitro (Klotz et al, 2006(Klotz et al, , 2007(Klotz et al, , 2008(Klotz et al, , 2010. Ergovaline was shown to be approximately 1,000-fold more potent and 5-fold more efficacious in causing vasoconstriction than lysergic acid (Klotz et al, 2006(Klotz et al, , 2007. Ergotamine and ergovaline reportedly have very similar contractile dose response curves (Klotz et al, 2007).…”
Section: Vasoconstrictive Potency and Efficacy Ofmentioning
confidence: 96%
“…Although potency and efficacy studies are routinely conducted on drugs, the study of ergot alkaloid potency and efficacy in the vasculature system of livestock has not received a great deal of attention. However, a series of studies have been published recently that examined the potency and efficacy of selected ergot alkaloids to induce constriction of the bovine lateral saphenous vein in vitro (Klotz et al, 2006(Klotz et al, , 2007(Klotz et al, , 2008(Klotz et al, , 2010. Ergovaline was shown to be approximately 1,000-fold more potent and 5-fold more efficacious in causing vasoconstriction than lysergic acid (Klotz et al, 2006(Klotz et al, , 2007.…”
Section: Vasoconstrictive Potency and Efficacy Ofmentioning
confidence: 98%
“…Accepted January 19, 2011 arundinaceum) toxicosis syndrome, and ergot alkaloids produced by the fungus Neotyphodium coenophialum have been demonstrated as causative agents of vasoconstriction (Strickland et al, 2009). Much of in the vitro research demonstrating this has been done using peripheral blood vessels (Williams et al, 1975;Solomons et al, 1989;Klotz et al, 2006), and of the few available in vivo reports investigating fescue toxicosis and ergot alkaloids (Walls and Jacobson, 1970;Harmon et al, 1991;Rhodes et al, 1991;Aiken et al, 2007), only Rhodes et al (1991) and Harmon et al (1991) have evaluated blood fiow to viscera. Delineating how ergot alkaloids are absorbed and transported from the digestive tract to the affected peripheral tissues has been elusive.…”
Section: Introductionmentioning
confidence: 94%
“…The authors determined that including yeast-derived cell wall improved serum prolactin post-calving in cows, and may alleviate concerns with high-alkaloid tall fescue, however, excretion of lysergic acid and ergovaline were not affected by the yeast-derived cell wall treatment. Klotz et al (2006) concluded that ergovaline is exponentially more powerful in stimulating vasoconstriction within in vitro bovine vasculature compared to lysergic acid, and more potent throughout host physiology as a whole. Ruminal microorganisms interact with feedstuffs in three established ways: those within the ruminal fluid, those loosely attached to feed particles and those firmly attached to feedstuffs (Cheng and McAllister 1997), thus breakdown of feedstuffs is essential for several types of microorganisms to access nutrients.…”
Section: B Ergot Alkaloids and Rumen Microbiomementioning
confidence: 99%